2010
DOI: 10.4103/0971-6580.72671
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Cadmium-induced oxidative stress in chicken by herbal adaptogens Withania somnifera and Ocimum sanctum

Abstract: The present study was carried out to evaluate the herbal adaptogens Withania somnifera and Ocimum sanctum on cadmium-induced oxidative toxicity in broiler chicken. Cadmium administration at the rate of 100 ppm orally along with feed up to 28 days produced peroxidative damage, as indicated by increase in TBARS, reduction in glutathione (GSH) concentration in liver and kidney, and increase in catalase (CAT) and superoxide dismutase (SOD) of erythrocytes. Herbal adaptogens Withania somnifera roots and Ocimum sanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Usually, decreased SOD activity was accompanied by decreased GSH-Px activity and increased lipid peroxidation in the same tissues. In contrast to the aforementioned results, Cd oral administration produced peroxidative damage in chickens, as indicated by increase in TBARS, reduction in GSH concentration in liver and kidney, but increased CAT and SOD activities were observed in erythrocytes [144]. Dietary nickel chloride is also shown to have a negative effect on SOD and other antioxidant enzymes (GSH-Px and CAT) in the intestine [145], cecal tonsil [146] or splenocytes [147].…”
Section: Toxicological Stressesmentioning
confidence: 39%
“…Usually, decreased SOD activity was accompanied by decreased GSH-Px activity and increased lipid peroxidation in the same tissues. In contrast to the aforementioned results, Cd oral administration produced peroxidative damage in chickens, as indicated by increase in TBARS, reduction in GSH concentration in liver and kidney, but increased CAT and SOD activities were observed in erythrocytes [144]. Dietary nickel chloride is also shown to have a negative effect on SOD and other antioxidant enzymes (GSH-Px and CAT) in the intestine [145], cecal tonsil [146] or splenocytes [147].…”
Section: Toxicological Stressesmentioning
confidence: 39%
“…Cd is accumulated and deposited in different organs of Japanese quail when administered orally [1,23]. Cd has a higher concentration in kidney than in the liver in broilers chicken when fed with dietary Cd [24]. Holoveska et al [25] observed a considerable growth in Cd levels in the liver of turkeys exposed to Cd.…”
Section: Discussionmentioning
confidence: 99%
“…Uyanik et al [13] noted a higher serum total protein and higher levels of globulin, AST and ALT in the broiler chicken orally exposed to Cd. Swapana et al [32] and Bharavi et al [24] observed a higher activity in the serum ALT, BUN, and creatinine in broiler chicken exposed to dietary Cd. San Ana et al [3] noted higher serum levels of ALT and AST and no change in ALP and creatinine in quails orally exposed to a dilution of 100 mg CdCl2/L distilled water for 28 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations